Estudo da transferência metálica no processo de soldagem MIG/MAG através da dimensão fractal do sinal de tensão - Carneiro, José Carlos de Souza (2005)
The techniques for estimating the fractal dimension of signals have been widely applied in the description of many physical systems, from studies of atmospheric turbulence, EEG signals, water systems to studies on the behavior of fractal surfaces fractured by impact. The analysis of the fractal dimension of complex phenomena has become an important tool to quantify the degree of irregularity of artificial or natural phenomena. In this paper we investigate the fractal dimension of the signal voltage of the arc processode MIG / MAG welding. The estimation technique used for calculating the fractal dimension of the signals in the study was the method box couting. It was verified that rapid changes in the values ​​of fractal dimension were associated with the phenomenon of metal transfer. Shows the signal analyzed in the time domain, the photographic pictures of the metal transfer, obtained by the technique of shadowgrafia, and programs used to obtain the graphs, calculating the fractal dimension as well as statistics of the signals welding. In the literature review is made a presentation of the electric arc welding considering only its physical aspects. It appears the method used in calculating the fractal dimension of signals. Are also treated the electron emission mechanisms, the process of welding MIG / MAG, the phenomenon of metal transfer in MIG / MAG and the forces involved during metal transfer.